Assembling carbon-coated α-Fe2O3 hollow nanohorns on the CNT backbone for superior lithium storage capability - Wang, Zhiyu (2013)
Novel hierarchical nanostructures composed of carbon coated a- Fe2O3 hollow nanohorns on carbon nanotube (CNT) backbones have been constructed by direct growth and thermal transformation of b-FeOOH nanospindles on CNTs, followed by carbon nanocoating. When evaluated as a potential anode material for lithiumion batteries, such hierarchical structures exhibit superior lithium storage capabilities by virtue of their advantageous structural features.